Exploring the Supply Chain Coordination Dimensions for Artemisinin-Based Combination Therapies in Uganda - Pross Oluka Nagitta; Marcia Mkansi (International Journal of Supply Chain Management, 2019)
ABSTRACT The aim of the study was to explore the micro, logistics, market and macro environment coordination dimensions, hence extending the existing framework to include external factors. Following a qualitative approach, multiple case study strategy was used. Specifically, four focus group discussions, each consisting of 8 respondents were conducted from four purposively selected hospitals. The respondents were selected using simple random sampling from representatives of Drug Therapeutic Management Committee (DTMC) for the purpose of exploring the supply chain coordination. Thereafter, the cross-case analysis was done to identify the key coordination mechanisms that are incorporated into the existing framework. To ensure construct validity of the research design, multiple sources of information were used. These were carefully organized in order to maintain the chain of evidence demonstrate that the study is reliable and ensure that it could be duplicated in the future. A number of coordination dimensions are identified from the focus group discussions, regrouped using appropriate and valid coding scheme. The study findings are limited to the four hospitals from the two most malaria endemic regions in Uganda. Another limitation is the novelty of the subject in health sector and the lack of data in this area. Further studies can be done from parts of the country to observe similarities and differences using quantitative approach. It is anticipated that the study will identify better ways of managing ACTs availability and probably save lives. The study paves way of understanding of supply chain coordination dimensions required to improve availability of ACTs in selected hospitals in Uganda. Keywords: Coordination, supply chain, dimensions, ACTs, Uganda